2014
DOI: 10.3389/fbioe.2014.00074
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Scaling and Cell Ratios in Multi-Organ in vitro Models of Human Metabolism

Abstract: Intelligent in vitro models able to recapitulate the physiological interactions between tissues in the body have enormous potential as they enable detailed studies on specific two-way or higher order tissue communication. These models are the first step toward building an integrated picture of systemic metabolism and signaling in physiological or pathological conditions. However, the rational design of in vitro models of cell–cell or cell–tissue interaction is difficult as quite often cell culture experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Common scaling approaches to date include direct miniaturization and allometric scaling of a variety of in vivo physical characteristics such as organ/tissue mass, blood flowrates, volumes and residence times 1, 11, 19, 20 . The focus of these approaches is to preserve the relative biomass scales of each organ (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Common scaling approaches to date include direct miniaturization and allometric scaling of a variety of in vivo physical characteristics such as organ/tissue mass, blood flowrates, volumes and residence times 1, 11, 19, 20 . The focus of these approaches is to preserve the relative biomass scales of each organ (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that allometric behaviour could be considered as a benchmark of physiological relevance 9,25 and a recent study shows that KL can be achieved in high density constructs 12 . The characteristic features of non-luminal organoids, that is high cell densities and their potential to therefore follow physiological metabolic scaling as well as to adopt the structural and functional features of mammalian organs on one hand, and their tendency to develop an oxygen deprived core on the other, appear to be in contrast.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods to solve the scaling issue and develop more physiologically relevant systems, such as allometric scaling and residence time of the blood in each organ . Allometric scaling considers the cell number, cell surface area, and metabolic rate between the body and the organs . Allometric ratios have been used as a scaling factor for the design of multiorgan chips.…”
Section: Remaining Challenges and Conclusionmentioning
confidence: 99%